2019
DOI: 10.1007/s40093-019-0272-8
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of dried sweet orange (Citrus sinensis) peel on humoral immune response of broiler chickens

Abstract: Purpose An experiment was conducted to evaluate the effect of dried sweet orange (Citrus sinensis) peel (DCSP) on humoral immune response of broiler chickens. Methods Four hundred 1-day-old Ross 308 broilers were distributed according to a completely randomized design into five treatments with four replicates of 20 chicks each. The following five dietary treatments were applied: control group with 0% DCSP; diet containing 1.5% DCSP from 1 to 21 days of age (starter phase) and from 1 to 42 days of age, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…2). This finding was consistent with a previously published report by Pourhossein et al (2019), in which OPP supplementation was shown to positively affect the Avian influenza titer, but it did not significantly affect the Newcastle disease titer. Although the antioxidant activity of OPP supplementation may play an important role in enhancing the humoral immune response through its antioxidant scavenging effect, its selective action on disease antibody titer is not well understood.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…2). This finding was consistent with a previously published report by Pourhossein et al (2019), in which OPP supplementation was shown to positively affect the Avian influenza titer, but it did not significantly affect the Newcastle disease titer. Although the antioxidant activity of OPP supplementation may play an important role in enhancing the humoral immune response through its antioxidant scavenging effect, its selective action on disease antibody titer is not well understood.…”
Section: Discussionsupporting
confidence: 93%
“…The bursa weight was not affected by the inclusion of dietary OPP (with or without xylanase supplementation; as shown in Fig. 1), and this result is consistent with previous research published by Pourhossein et al (2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It has been documented that about 80% of kitchen wastes, largely food wastage are fed to pigs in China, although direct feeding of kitchen waste has not been without restriction in China, arising from the concern of foot and mouth disease [46] Processing of agricultural solid wastes could enhance their value for feeding pigs [47,48]. The effect of dried sweet orange (Citrus sinensis) peel has been tested on humoral immune response of broiler chickens [49] as well as maize replacement and its effect evaluated on growth performance and carcass qualities of broiler chickens [50], instead of allowing them to accumulate and constitute a nuisance as agricultural solid wastes.…”
Section: Effective Management Of Agricultural Solid Wastesmentioning
confidence: 99%